Endoscopic resection of upper gastrointestinal lesions using the colonic Ovesco full-thickness resection device: Retrospective observational case series of 22 cases - Nilsson, Jan-Erick; de Graaf, Wilmar; Koch, Arjun Dave (Endoscopy International Open, 2023)
Background and study aims The endoscopic full-thickness resection (EFRT) device (FTRD) has been shown to have acceptable outcomes in regard to efficacy and safety in the resection of colorectal lesions. Data on its use in the upper gastrointestinal tract are limited to small case series.Patients and methods All consecutive patients undergoing endoscopic full-thickness resection of gastric or duodenal lesions at our institutions were analyzed retrospectively for a primary endpoint of technical success.Results A total of 22 patients with duodenal and gastric lesions underwent EFTR between June 2018 and February 2022. Technical success was achieved in 20 of 22 (91 %) of the procedures. Indications for EFTR were: subepithelial tumor (n = 14), mucosal lesion (n = 5), scar resection (n = 2), and EFTR of endoscopic submucosal dissection (ESD) resection base (n = 1). The FTRD could be advanced to the lesion in all 22 cases (100 %). No dilation of the upper esophageal sphincter (UES) or pylorus was required to pass the device. There were 14 cases of gastric lesions and eight duodenal. One subepithelial lesion was too big for the cap and one scar could not be sucked into the cap. One lesion (gastrointestinal stromal tumor) was removed at second procedure with the ESD technique, including over-the-scope clip. The R0 resection rate for deployed clips was 90 % (18 of 20). There were two superficial esophageal tears from FTRD insertion that required no therapy. No bleeding occurred during the postoperative period.Conclusions Upper gastrointestinal EFTR using the colonic Ovesco FTRD is feasible without pre-dilation of the upper esophageal sphincter or pylorus. This study further confirms acceptable efficacy and safety in upper gastrointestinal use.